2021
DOI: 10.1016/j.rbmo.2021.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Absence of SARS-CoV-2 (COVID-19 virus) within the IVF laboratory using strict patient screening and safety criteria

Abstract: Research Question: In the early stages of the COVID-19 pandemic, IVF clinics stopped the majority of patient treatment cycles to minimize the risk of disease transmission. The risk of SARS-CoV-2 viral exposure and potential cross contamination within the IVF lab remains largely unclear. To that end, the objective of this study was to examine follicular fluid (FF), culture media (M) and vitrification solution (VS) for SARS-CoV-2 in an IVF lab. Design : Prospective clinical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Our results are consistent with research that confirmed the absence of viral products or contamination in embryology lab specimens from COVID negative patients [14]. Additionally, a small case reports suggest that the virus is not present in oocytes of COVID positive patients [15], or in semen of COVID recovered patients [16,17], but additional research is necessary.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with research that confirmed the absence of viral products or contamination in embryology lab specimens from COVID negative patients [14]. Additionally, a small case reports suggest that the virus is not present in oocytes of COVID positive patients [15], or in semen of COVID recovered patients [16,17], but additional research is necessary.…”
Section: Discussionsupporting
confidence: 91%
“…These include exposure to virus shed by asymptomatically infected medical and laboratory personnel during various procedures (handling of gametes, assisted conception, embryo culture, biopsy, vitrification, and thawing), or by infected patients (for example, a male patient contaminating a sample vial during sperm collection, via regular exhalation). The data presented here should inform best practices in the ART clinic during the COVID-19 pandemic, further building on existing recommendations for safety and risk mitigation [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 86%
“…have shown the co-expression of ACE2 and TMPRSS2 proteins in the mature eggs (MII oocytes), embryos and blastocysts, indicating that these gametes and embryos are potentially susceptible to SARS-CoV-2 infection if exposed to the virus. [ 2 ] We could not find any study evaluating the lag period between blood positivity and follicular fluid positivity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Another report also studied the follicular fluid from 300 patients and these all samples were negative for SARS-CoV-2 infections. [ 2 ] Another report on SARS-CoV-2 infected women undergoing assisted reproductive technology (ART) also showed that, the absence of viral RNA in the cumulus cells, endometrial tissue and follicular fluid samples. [ 6 ] COVID-19 infection or the BNT162b2 mRNA vaccination has no measurable detrimental effect on the function of the ovarian follicle.…”
Section: Discussionmentioning
confidence: 99%